PARTITIONING OF NICKEL, COBALT AND MANGANESE BETWEEN SILICATE PEROVSKITE AND PERICLASE: A TEST OF CRYSTAL FIELD THEORY AT HIGH PRESSURE - Malavergne V.; Guyot F.; Yanbin W.; Martinez I. (My University, 1997)
Magnesium-normalised nickel, cobalt and manganese partition coefficients (Kd-Ni, Kd-Co, and Kd-Mn) between silicate perovskite and periclase have been measured experimentally in multi-anvil press and diamond-anvil cell samples at pressures and temperatures ranging between 26 and 70 GPa and between 1500 K and ~ 3000 K, respectively. The results show that, over all the investigated pressure range, Kd-Mn < Kd-Co # Kd-Ni. At 1500 K and 26 GPa, the following values have been obtained: Kd-Mn = 0.7, Kd-Co = 4.8 and Kd-Ni > 33. The measured values of the partition coefficients are compared with the analytical results of Kesson and Fitzgerald, reinforcing the idea that the compositions of inclusions in diamonds of ultra-deep origin are compatible with a pyrolitic model of the lower mantle. A simple crystal field model, combined with a correction of size effects, is shown to be adequate for rationalizing the partitioning behaviour. This model also allows prediction of pressure and temperature effects on the distribution of transition metals between silicate perovskite and periclase. The consequences of possible spin transitions in periclase and silicate perovskite are discussed; if they occurred, such electronic transitions would have dramatic effects on partitioning behaviour.
Keywords: HIGH-PRESSURE RESEARCH; MANTLE; NICKEL; COBALT; MANGANESE; ELECTRON MICROSCOPY